2015
DOI: 10.1002/acp.3147
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice Recommendations Still Fail to Result in Action: A National 10‐Year Follow‐up Study of Investigative Interviews in CSA Cases

Abstract: SummaryThe present study examined a national sample of Norwegian investigative interviews in alleged child sexual abuse cases (N = 224) across a 10‐year period (2002–2012), in order to decide whether practice had improved over the decade in terms of the types of questions asked. The results indicate that the frequency of open‐ended, directive, option‐posing, and suggestive questions asked was unchanged during the 10‐year period, but that the frequency of repeated questions had increased significantly. When ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 31 publications
4
45
0
2
Order By: Relevance
“…Of course, such training and feedback would be relevant not only for Dutch interviewing practice but also for all countries where child interviewing is not up to par. Indeed, our results align well with interviewing practices in other countries in which the NICHD Protocol is also not applied (e.g., Australia: Powell & Hughes‐Jones, ; Finland: Korkman, Santtila, Westeråker, & Sandnabba, ; New Zealand: Wolfman et al, ; and Norway: Johnson et al, ). Specifically, what is mainly found in these countries is that invitations are also rarely used, suggesting that intensive training and feedback is required to improve interview quality.…”
Section: Discussionsupporting
confidence: 85%
“…Of course, such training and feedback would be relevant not only for Dutch interviewing practice but also for all countries where child interviewing is not up to par. Indeed, our results align well with interviewing practices in other countries in which the NICHD Protocol is also not applied (e.g., Australia: Powell & Hughes‐Jones, ; Finland: Korkman, Santtila, Westeråker, & Sandnabba, ; New Zealand: Wolfman et al, ; and Norway: Johnson et al, ). Specifically, what is mainly found in these countries is that invitations are also rarely used, suggesting that intensive training and feedback is required to improve interview quality.…”
Section: Discussionsupporting
confidence: 85%
“…Research has highlighted the discrepancy between endorsed or reported practices and actual interviewer behavior. For example, a 10‐year follow‐up study of forensic interviews in CSA investigations revealed the consistent use of problematic interviewing strategies in a sample of Norwegian interviewers despite proper training (Johnson et al, ). In addition to assessing forensic interviewers' actual practices, future research should also include researchers and forensic psychologists who frequently serve as expert witnesses in CSA cases.…”
Section: Discussionmentioning
confidence: 98%
“…Although our sample largely comprised interviews from the late 1990s, similar results would likely be obtained if present day NICHD Protocol interviews were compared with those conducted by less intensely monitored non-NICHD interviewers, who may well be aware of best interviewing practice but fail to change their behavior accordingly. A recent Norwegian study documented that, despite extensive investment in the training of forensic interviewers across the country, neither the use of undesirable practices (e.g., suggestive prompts) nor the use of recommended practices (e.g., openended questions) changed over a 22-year period (1990-2012) (Johnson et al 2015). Thus, it is possible (albeit unfortunate) that present day interviews may resemble those we studied.…”
Section: Limitationsmentioning
confidence: 89%